A new catalytic merit for prediction catalytic potential of 2D materials in LiO2 batteries: Theoretical investigation and experimental identification - Geng Cheng; Wenpei Li; Chengyan Liu; Jie Gao; Jun-Liang Chen; Jianhua Zhou; Xiaoyang Wang; Lei Miao (Journal of Materiomics)
Two-dimensional (2D) materials such as metal chalcogenides have great potential as cathode catalyst materials for lithium oxygen batteries (LOBs) due to their large specific surface area and stable chemical properties. However, thus far, due to the lack of theoretical prediction methods, huge load on catalytic synthesis and performance evaluation is concerned. Herein, we reported a theoretical method for 2D metal chalcogenides as catalysts for LOBs using first principles density functional theory (DFT) calculations. We extracted key parameters that affect the overpotential, including Li–X bond energy (X represents chalcogen elements) and catalyst lattice constant, and theoretically predicted the catalytic performance. The DFT calculation results indicate that MoS2 with appropriate Li–X bond energy and lattice constant has the lowest theoretical overpotential, and its cyclic stability should be higher than other materials under the same conditions. Significantly, we experimentally validated the theoretical predictions presented above. The experimental results shows that pure MoS2 with 2H phase can stably work for more than 220 cycles at a current density of 500 mA/g, and the actual overpotential is lower than other metal chalcogenides. This work provides a swift pathway to accelerate searching high performance catalytic in LOBs.